Entrepreneurial orientation and corporate social responsibility performance: An empirical study of state‐controlled and privately controlled firms in China. (18th December 2019) - Zhuang, Yiming; Lee, Younggeun; Chang, Xinyue; Kim, Renee B.
Abstract: In this paper, we examine the role of a firm's entrepreneurial orientation (EO) in the advancement of corporate social responsibility (CSR) performance. We argue that a firm's innovativeness, proactiveness, and risk‐taking would lead it to employ more socially responsible practices and generate benefits to society. Moreover, we theorize that this influence would differ, depending on the firm ownership. Specifically, our argument is based on the Chinese context where state‐controlled firms dominate the economy. We test our hypotheses by utilizing secondary data on 738 Chinese public firms over an 8‐year period (2008–2015). Our empirical results demonstrate a positive and significant relationship between EO and CSR performance among state‐controlled firms. However, this relationship is not significant among privately controlled firms.